THE CORPORATE BOND YIELDS IN INDONESIA - Mohamad Adam; Reza Gasharma; Mutiarany Nuary (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2015)
This research aims to evaluate the corporate bond yields in Indonesia. Population used in this research are all issuer companies were listed in BEI. The sample in this research is 16 bonds from 16 companies. The result in this research find that the interest rates, bond rating and variable of DER have significant relationship on bond yields. Inflation rates and firm size proven have contrast relationship on bond yields.Keywords : bond yields, interest rates, debt to equity ratio